BALANCING SENSORY STIMULATION/DEPRIVATION FROM THE ENVIRONMENT IN HEALTH-FORMING TECHNOLOGIES - Anatolie BACIU (Academy of Sciences of Moldova, 2024)
The Medicine of the near future will develop not only along the path of improving diagnostics, treatment, rehabilitation, but also through the development of technologies for the formation (promotion) of health, human enhancement, and work productivity. It is clear that, due to their highly specialized multimodal sensory sensitivity, living systems are flexibly and plastically remodeling, changing structure and function in a completely physiological manner. Therefore, an attempt was made to conceptually and experimentally test the possibility of balancing sensory stimulation and sensory deprivation in their close dependence on the circadian sleep-wake cycle. A group of examined individuals practiced a mandatory evening walk in the park area for 40-60 minutes for 15 days and sensory deprivation by turning off artificial lighting, television, computer, gadgets and any other sensory signaling streams in the evening, starting from 8:00 pm and until going to bed (10:00 pm). The Facial Action Coding System (FACS) was applied to classify, qualitatively and quantitatively evaluate the facial psychomotor reactions of a person in the dynamics of his emotional state and by this tool indirectly reflects the balance of the activating and rewarding systems. The results obtained suggest that after a 15-day course of "Balancing Sensory Stimulation/Deprivation" the examined individuals maintain a positive emotional state during virtual immersion in a safe environment in the morning after a night's sleep compared to baseline measurements. It is strategically important to optimize labor, work, educational activities, prevent overload and fatigue, it is necessary to ensure the formation of a balance of circadian sensory stimulation and deprivation in combination with activities that improve the architecture and quality of sleep.